استعمالات مـا في اللغة العربيـة دراسة تطبيقية في سورة الاسراء - بن حضرية عبد الرزاق; بالعقون سهام (University of Eloued جامعة الوادي, 2025)
الملخص: تناولت هذه المذكرة دراسة تحليلية نحوية-دلالية لاستعمالات أداة "ما" في اللغة العربية، مع التركيز على سورة الإسراء ضمن منهجية وصفية تحليلية دلالية. واستعرضت الدراسة جميع مواقف أداة "ما" في السورة (32 مرة) وفق رواية ورش عن نافع (طبعة مجمع الملك فهد، 1438 هـ)، وصنفت هذه الاستخدامات إلى: ما الموصولة (8 مرات). ما الزائدة (11 مرة). ما النافية (8 مرات). ما المصدرية (مرتان). غابت أشكال أخرى مثل "ما الحجازية" و"ما التعجبية"، وهو أمر ذو دلالة أسلوبية تتناسب مع طبيعة السورة التي تتضمن صيغًا تقريرية وتشريعية بارزة. أثبتت الدراسة أن تنوّع استخدامات "ما" في السورة ليس عشوائيًا، بل يخدم أغراضًا بلاغية تدعم مفاهيم الشمولية (في الملك والجزاء)، التوكيد (في التوحيد ووحدة الأسماء الحسنى)، والحصر (في وظائف الرسالة والعقاب). كما أوضحت أن اختيار النوع النحوي المناسب لكل سياق يعكس إعجازًا لغويًا، حيث تحمل الأداة الصغيرة وظائف بلاغية عميقة تحقق التوازن بين الجانب النحوي والمقصد الشرعي. Summary: - This research presents a syntactic-semantic analysis of the particle "mā" in the Arabic language, focusing on its application in Surat al-Isrāʾ (Quran 17). Utilizing a descriptive-analytical approach, the study transcends formal grammatical classification to explore the deeper semantic and rhetorical functions of "mā" within its Qur'anic contexts, particularly how it serves the surah's theological and legislative objectives. A comprehensive survey of all 32 instances of "mā" in the surah—based on the canonical Warsh ʿan Nāfiʿ recitation (King Fahd Complex, 1438 AH)—categorized them as follows: •Relative mā (8 instances), •Emphatic/expletive mā (11 instances), •Negating mā (8 instances), •Nominalizing mā (2 instances). Notably absent are forms such as Hijazi mā and exclamatory mā—a deliberate stylistic choice reflecting the surah’s predominantly declarative and legislative tone. The study demonstrates that the variation in "mā" usage is not random but rhetorically motivated, reinforcing concepts of comprehensiveness (in divine dominion and recompense), emphasis (in divine unity and the integrity of the Beautiful Names), and restriction (in prophetic mission and divine punishment). Ultimately, the precise selection of "mā" type in each context exemplifies a layer of linguistic inimitability (iʿjāz), where this seemingly minor morpheme plays a major role in harmonizing grammatical function with theological intent.
مذكرة ليسانس. 2025. ليسانيات عامة
Keywords: mā; Sūrat al-Isrāʾ; Qur’ānic syntax; semantics; rhetoric; Warsh recitation; ما، سورة الإسراء، النحو القرآني، الدلالة، البلاغة، ورش عن نافع